Heterogeneous Photocatalysis for Advanced Water Treatment: Materials, Mechanisms, Reactor Configurations, and Emerging Applications - Maria Paiu; Doina Lutic; Lidia Favier; Maria Gavrilescu (Applied Sciences)
Heterogeneous photocatalysis has emerged as a versatile and sustainable technology for the degradation of emerging contaminants in water. This review highlights recent advancements in photocatalysts design, including band gap engineering, heterojunction formation, and plasmonic enhancement to enable visible-light activation. Various reactor configurations, such as slurry, immobilized, annular, flat plate, and membrane-based systems, are examined in terms of their efficiency, scalability, and operational challenges. Hybrid systems combining photocatalysis with membrane filtration, adsorption, Fenton processes, and biological treatments demonstrate improved removal efficiency and broader applicability. Energy performance metrics such as quantum yield and electrical energy per order are discussed as essential tools for evaluating system feasibility. Special attention is given to solar-driven reactors and smart responsive materials, which enhance adaptability and sustainability. Additionally, artificial intelligence and machine learning approaches are explored as accelerators for catalyst discovery and process optimization. Altogether, these advances position photocatalysis as a key component in future water treatment strategies, particularly in decentralized and low-resource contexts. The integration of material innovation, system design, and data-driven optimization underlines the potential of photocatalysis to contribute to global efforts in environmental protection and sustainable development.